Soyghurt Potentially Controls the Level of sFlt1 and PLGF in Preeclampsia Maternal Serum-Induced Placental Trophoblast Cell in vitro - Khairani AF; Lantika UA; Ramadhanti J; Bashari MH; Shalannandia WA; Wikayani TP; Achadiyani A; Ritonga MA (Dove Medical Press, 2024)
Astrid Feinisa Khairani,1 Uci Ary Lantika,2 Julia Ramadhanti,1 Muhammad Hasan Bashari,1,3 Widad Aghnia Shalannandia,1 Tenny Putri Wikayani,4 Achadiyani Achadiyani,1 Mulyanusa Amarullah Ritonga5 1Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Jatinangor, West Java, Indonesia; 2Department of Biomedical Sciences, Faculty of Medicine, Universitas Islam Bandung, Bandung, West Java, Indonesia; 3Research Centre of Oncology and Stem Cell, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, Indonesia; 4Culture and Cytogenetic Laboratory, Universitas Padjadjaran, Bandung, West Java, Indonesia; 5Department of Obstetrics and Gynecology, Hasan Sadikin General Hospital, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, IndonesiaCorrespondence: Astrid Feinisa Khairani, Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Jalan Raya Bandung - Sumedang Km 21, Jatinangor, West Java, 45363, Indonesia, Tel +62-22-779559445363, Email astrid.khairani@unpad.ac.idPurpose: To observe the effect of soya yoghurt (Soyghurt), which is high in flavonoid substance, on the expression of preeclampsia biomarkers (sFLT-1 and PLGF) on preeclampsia serum-induced trophoblast primary cell culture isolated from placental tissue.Methods: The trophoblast primary culture was induced by preeclampsia serum (10%). The Soyghurt treatment was performed with 2.5%, 5%, and 7.5% Soyghurt supernatant concentrations in culture media. The expression of preeclampsia markers, sFLT-1 and PLGF, were evaluated using ELISA.Results: Expression of sFLT-1 on preeclampsia-induced cell culture treated with Soyghurt was significantly lowered compared to the untreated group (p< 0.01). However, no significant difference was observed in the PLGF levels of all groups induced by preeclampsia serum (p> 0.05).Conclusion: This study demonstrates the potential effect of Soyghurt's in balancing preeclampsia marker expression by inhibiting the expression of sFLT-1 in preeclampsia serum -induced trophoblast cells.Keywords: preeclampsia, PLGF, sFLT-1, soya yoghurt, trophoblast